As mediações terapêuticas e seu uso na formação de trabalhadores da saúde: o sofrimento psíquico familiar - Antonieta Pezo, María (Revista Brasileira de Psicodrama, 2020)
In the formation of health workers, therapeutic mediations such as dramatization and group pictogram are tools which enable access to psychological capacities registered in the body through sensations and perceptions. Dramatization and pictographs potentialize the emergence of these new psychological capacities, allowing access to unique records that would not appear when asked to recall, tell or say; and encourage verbalization, the symbolization of what has been excluded from consciousness. It is essential to recognize and reflect on what is done, said, perceived, felt, heard, and thought.